Comparison of two hydrodynamic models for their rain-on-grid technique to simulate flash floods in steep catchment - Godara, Nitesh; Bruland, Oddbjørn; Alfredsen, Knut (Frontiers in Water, 2024)
In this study, two hydrodynamic models, TELEMAC-2D and HEC-RAS 2D were compared for their Rain-on-Grid (RoG) technique with a particular focus on runoff generation processes in a small and steep catchment. Curve number (CN) method was applied in both the models to simulate two single storm events up to 20 hours duration. Whereas Green-Ampt Redistribution (GAR) method was additionally applied in HEC-RAS 2D for a multi-peak flood event with sustained flow between the peaks. CN and GAR methods were compared for this flood event, and a sensitivity analysis of the GAR parameters was also done. Moreover, the two models were compared for their calibration process, computational time, mesh size and shape, model availability in general, as well as the results including inundated areas, water depths and velocity. The results indicate that both the models are capable of reproducing short duration single storm floods. NSE and R 2 for both models ranged from 0.70 to 0.90 and from 0.93 to 0.95. However, the models struggled to reproduce the long-duration multi-peak flood event.The sensitivity analysis showed that the results are not very sensitive to the two GAR parameters which are responsible to influence the flow of the second peak in the flood event.Neither the CN nor the GAR infiltration method successfully replicated such events because the hydraulic models permanently lose infiltrated water from the domain. The returned subsurface flow significantly contributes to river flow during these flood events; however, neither model incorporates a return flow algorithm.